PENERAPAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PECAHAN PADA SISWA SEKOLAH DASAR - Yulianti, Sri (Media Pendidikan Matematika, 2013)
Teacher does not build a connection between the concept would be taught and the prior knowledge. So that the students often memorize the concept given and solve a problem procedural. As the result, students have weak understanding about a concept and its application.This study aimed to describe the instructional steps in RME which to increase the students understanding about fraction, and how student understanding of grade 4th of SDN 6 Pringgabaya about fraction through the application with RME. This study was classroom action research (PTK).The result shows that the instructionwith RME was conducted based on the instructional steps to increase the students’ understanding about fraction concept. These steps involve: (1) understanding the contextual problem deal with fraction, (2) solving in group the contextual problem about the fraction by using and modeling the manipulative materials provided, (3) comparing and discussing the student work by asking one group to present their work, and (4) concluding the topic that have been learned and discussed.The result of test, the percentage of average score of students is ³ 65 for Action II. The precise figure is 26 of 32 students participated. The means that the understanding of students about the fraction topic is increased